Transcription factors Foxa1 and Foxa2 are required for adult dopamine neurons maintenance - Domanskyi, Andrii; Alter, Heike; Vogt, Miriam A.; Gass, Peter; Vinnikov, Ilya A. (Frontiers in Cellular Neuroscience, 2014)
The proteins Foxa1 and Foxa2 belong to the forkhead family of transcription factors and are involved in the development of several tissues, including liver, pancreas, lung, prostate, and the neural system. Both Foxa1 and Foxa2 are also crucial for the specification and differentiation of dopamine (DA) neurons during embryonic development, while about 30% of mice with an embryonic deletion of a single allele of the Foxa2 gene exhibit an age-related asymmetric loss of DA neurons and develop locomotor symptoms resembling Parkinson’s disease (PD). Notably, both Foxa1 and Foxa2 factors continue to be expressed in the adult dopamine system. To directly assess their functions selectively in adult DA neurons, we induced genetic deletions of Foxa1/2 transcription factors in mice using a tamoxifen inducible tissue-specific CreERT2 recombinase expressed under control of the dopamine transporter (DAT) promoter (DATCreERT2). The conditional DA neurons-specific ablation of both genes, but not of Foxa2 alone, in early adulthood, caused a decline of striatal dopamine and its metabolites, along with locomotor deficits. At early pre-symptomatic stages, we observed a decline in aldehyde dehydrogenase family 1, subfamily A1 (Aldh1a1) protein expression in DA neurons. Further analyses revealed a decline of aromatic amino acid decarboxylase (AADC) and a complete loss of DAT expression in these neurons. These molecular changes ultimately led to a reduction of DA neuron numbers in the substantia nigra pars compacta (SNpc) of aged cFoxa1/2-/- mice, resembling the progressive course of PD in humans. Altogether, in this study, we address the molecular, cellular and functional role of both Foxa1 and Foxa2 factors in the maintenance of the adult dopamine system which may help to find better approaches for PD treatment.